Does a perception of increased blood safety mean increased blood transfusion? An assessment of the risk compensation theory in Canada - Wilson Kumanan; Amin Mo; Tinmouth Alan; Hébert Paul (BMC, 2004)
Abstract Background The risk compensation theory is a widely used concept in transport economics to analyze driver risk behaviour. This article explores the feasibility of applying the theory in blood transfusion to raise important questions regarding the increased blood safety measures and their possible effects on blood usage (e.g., the appropriateness in transfusion). Further, it presents the findings of a pilot survey of physicians in Canada. Discussion While studies have attempted to define transfusion appropriateness, this article argues that if the risk compensation theory holds true for transfusion practice, physicians may actually be transfusing more. This may increase the possibility of contracting other unknown risks, such as the variant Creutzfeldt-Jakob Disease (vCJD), as well as increasing the risk of non-infectious transfusion risks, such as transfusion reactions. Summary A much larger study involving psychosocial assessment of physician decision making process to fully assess physician behaviour within the context of risk compensation theory and transfusion practice in Canada is needed to further explore this area.